New species of Thraulodes Ulmer, 1920 (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) from Northeastern Brazil - Campos, Rogerio [UNESP]; Mariano, Rodolfo (Magnolia Press, 2019)
Two new species of the genus Thraulodes Ulmer are described from the Brazilian Atlantic rainforest and Caatinga biomes from the state of Bahia, northeastern Brazil. Thraulodes catoles sp. nov. is described based on the male imago and can be distinguished from all other congeners by possessing the forewings with three cross veins basal to bullae; a reddish band on the apex of the foreleg femora; styliger plate with digitiform dorsal extension and penes with an apicolateral ear, long spines, lapel on inner margin and lateral pouch present. Thraulodes calori sp. nov. is described based on male and female imagos and can be diagnosed by the three weak cross veins basal to bullae on forewings; the apex of styliger plate rounded without medial projection with lateral margins acuminated; and the penes short, wide and without lateral pouch. The key to Thraulodes from Brazil was updated to include the new species described for the genus.
Keywords: mayflies; biodiversity; taxonomy; Neotropical; South American